2006
DOI: 10.1177/0310057x0603400105
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arteriovenous Malformation Causing Massive Haemoptysis and Complicated by Coronary Air Embolism

Abstract: We report the case of a 20-year-old man with possible Osler-Rendu-Weber syndrome (hereditary haemorrhagic telangiectasia) who developed an episode of massive haemoptysis from a bleeding pulmonary arteriovenous malformation in the left lower lobe of his lung. During the acute haemorrhage, he also appeared to suffer a coronary air embolism, possibly due to introduction of air into the bleeding arteriovenous malformation during intermittent positive pressure ventilation through the endotracheal tube. His electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The coil migration to bronchi may cause two types of troubles: a bronchial pulmonary artery fistula and a bronchial foreign body. Since the coil was placed in the vessel, fistula formation by coil migration may induce fatal massive hemoptysis [ 12 ], air embolism [ 13 ] or retrograde infection to the blood stream. It has also been reported that the metallic coil as a foreign body induced cough and hoarseness [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coil migration to bronchi may cause two types of troubles: a bronchial pulmonary artery fistula and a bronchial foreign body. Since the coil was placed in the vessel, fistula formation by coil migration may induce fatal massive hemoptysis [ 12 ], air embolism [ 13 ] or retrograde infection to the blood stream. It has also been reported that the metallic coil as a foreign body induced cough and hoarseness [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…12,16,17 If the patient must undergo anesthesia, steps should be taken to avoid the introduction of air emboli in the intravenous line due as pulmonary AVMs may have right-to-left shunting that can result in stroke. 8,10,19 For example, a bubble trap was utilized in this patient when she underwent anesthesia during her hospitalization at our institution. 20 The anesthetic selected should avoid elevated blood pressures as it may result in AVM rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Our case was assumed to be congenital PAVM without any apparent acquired origin, although there were no abnormalities in skin, oral, and nasal mucosa. About 13% to 15% of PAVM show symptoms such as dyspnea, hemoptysis, or hemothorax related to the intrapulmonary arteriovenous shunt [4,5]. In cases with severe symptomatologies, hemorrhage from a ruptured PAVM and various neurological complications such as cerebrovascular accidents from brain abscess and paradoxical embolism may occur [2,6].…”
Section: Discussionmentioning
confidence: 99%